ANALISIS KEBUTUHAN BAHAN AJAR ELEKTRONIK BERBASIS CERITA ANAK DALAM PEMBELAJARAN IPAS SISWA KELAS IV SEKOLAH DASAR - Surya Arseni, Dian; Ni Nyoman Kurnia Wati; I Gede Arya Wiradnyana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Learning Natural and Social Sciences (IPAS) in fourth grade of elementary school requires an engaging approach that is in line with the characteristics of student development. This is important because students aged 9-10 years are more easily engaged with visual and fun content, which is in line with their cognitive and emotional developmental stages. Electronic teaching materials based on children's stories offer an innovative solution in improving students' understanding and interest in learning. It is expected to make learning more lively and easier to follow, so that students are more enthusiastic in participating in learning. This study aims to analyze the need for electronic teaching materials based on children's stories in fourth grade of elementary school's IPAS learning. The method used is a literature study by reviewing various relevant library sources, using sources reviewed including previous research on story-based learning, technology integration in elementary education, and the use of children's stories in learning. The results of the study indicate that children's stories have the potential to facilitate contextual and fun learning, while electronic teaching materials offer flexibility and interactivity. The combination of the two can strengthen the process of understanding the concept of IPAS and student information retention, so that the need for its development is increasingly clear to support the achievement of learning objectives.